Clinical assessment of the severity of chronic hand eczema: correlations between six assessment methods - Duman, Nilay; Uzunali, Erol (The European Research Journal, 2015)
Objective. The severity of hand eczema (HE) can be assessed via numerous methods, however, a standard method remains lacking. Furthermore, correlations between the various methods are not known. The purpose of the study was to evaluate the correlations between six different methods used for assessing the severity of chronic HE. Method. The study included 100 patients with chronic HE. The severity of HE was assessed using the Hand Eczema Severity Index (HECSI), Physician Global Assessment (PGA), Dermatology Life Quality Index (DLQI), Photographic Guide (PG), Osnabrueck Hand Eczema Severity Index (OHSI), and Investigators’ Global Assessment (IGA). Furthermore, correlations between the 6 methods were determined. Results. There was a strong correlation between HECSI, and OHSI, mTLSS, PG, and IGA, and between IGA, and PG and OHSI (P < 0.001). There was a moderate correlation between DLQI and PGA (P < 0.001), whereas correlations between DLQI and the other scales were weak. The females had lower quality of life, although gender was not associated with disease severity according to the other scales. Conclusion. Overall, the six methods used for assessing the severity of HE were significantly positively correlated. Females had lower quality of life, but the severity of HE assessed via the other five scales did not vary according to gender. The weakest correlation was between DLQI and all other scales.